The level of organizational commitment among lecturers in technical and vocational colleges in Iran - Nazari, Khosrow; Lope Pihie, Zaidatol Akmaliah; Basri, Ramli; Idris, Khairuddin (Universiti Putra Malaysia Press, 2012)
The main purpose of this study was to determine the level of organizational commitment among 295 lecturers of Technical and Vocational Colleges in four provinces of Fars, Khuzestan, Boushehr, and Kohgilouyeh and Boyerahmad in Iran. A survey-based descriptive research design was employed. Data were analyzed using a descriptive analysis. In addition, ANOVA was utilized to determine lecturers’ commitment based on demographics. Lecturers’ commitment as the core workforce of higher education institutions is important. Educational leaders, policy makers and academic administrators should take the necessary measures to make them highly committed. The findings revealed that the perception level of respondents was rated from low, moderate to high. Meanwhile, significant differences were observed in the respondents’ commitment by their education level, monthly income and age. The relevant literature shows little studies pertaining to university lecturers’ commitment of higher learning institutions in Iran. Thus, the current study has contributions to improving the understanding of organizational commitment issue.